Procedures in the translation of proper names in Harry Potter and the Goblet of Fire into Malay - Atikah Zabir,; Haslina Haroon, (Penerbit Universiti Kebangsaan Malaysia, 2018)
In fantasy fiction, names play a fundamental role in portraying the characters’ personality traits and identity. Names are also sometimes chosen to create certain effects. The fact that names may carry meaning raises the question of how names are dealt with in translation. This issue is especially pertinent in the case of the Harry Potter novels in which many of the names have associative meanings. In view of this, the aim of this study is to determine the procedures used in the translation of some of the proper names in the novel ‘Harry Potter and The Goblet of Fire’ into Malay. The study also aims to discuss the effects resulting from the use of the translation procedures. To carry out the study, the proper names in the novel are first identified based on the definition of proper names by Fernandes (2006). Next, the names are mapped to their Malay counterparts. The procedures for the translation of proper names proposed by Fernandes (2006) are then used to analyse how the names are translated into Malay. Finally, the concept of ‘translation loss’ by Hervey and Higgins (1992) is used to determine the effects resulting from the use of the translation procedures. The analysis reveals that a number of different procedures are used to translate the names into Malay. The procedures used have resulted in the loss of hidden meanings in the names, the loss of the creative aspect of the names and the loss of the casual style of the original.